2022
DOI: 10.1002/eom2.12205
|View full text |Cite
|
Sign up to set email alerts
|

The promising solar‐powered water purification based on graphene functional architectures

Abstract: Solar‐powered water purification is able to gain freshwater from nonedible water by harnessing inexhaustible and pollution‐free sunlight energy, which is undergoing booming development to address the global water shortage. Due to the fascinating properties, numerous graphene‐based materials were devoted to the solar‐powered system from interfacial solar‐steam generation, towards solar pollutants degradation and even atmospheric water harvesting. Therefore, manipulations on graphene including chemical regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 155 publications
0
17
0
1
Order By: Relevance
“…Several strategies have been proposed to improve the efficiency of SSG by engineering photothermal materials to have strong light absorption over a wide-frequency band (0.2–3 μm) and high photothermal conversion efficiency, as well as designing a substrate to have good thermal insulation to avoid excessive heat loss and capability to supply water to hot regions. They include chemical regulation ,, and structural engineering , of the photothermal materials as well as solar evaporator design. , Chemical regulation of photothermal materials is carried out by introducing different elements or functional groups into the primary photothermal material or compositing two or more photothermal materials. Structural engineering includes assembling photothermal materials to specific architecture for the efficient use of the materials in the solar steam generation system.…”
Section: Solar Thermal Conversion Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several strategies have been proposed to improve the efficiency of SSG by engineering photothermal materials to have strong light absorption over a wide-frequency band (0.2–3 μm) and high photothermal conversion efficiency, as well as designing a substrate to have good thermal insulation to avoid excessive heat loss and capability to supply water to hot regions. They include chemical regulation ,, and structural engineering , of the photothermal materials as well as solar evaporator design. , Chemical regulation of photothermal materials is carried out by introducing different elements or functional groups into the primary photothermal material or compositing two or more photothermal materials. Structural engineering includes assembling photothermal materials to specific architecture for the efficient use of the materials in the solar steam generation system.…”
Section: Solar Thermal Conversion Materialsmentioning
confidence: 99%
“…Most of the review papers published recently discussed the designs of an SSG system and identified that the photothermal effect, water supply, and thermal management are the three key factors for an efficient SSG system for future development. Ibrahim et al, Hu et al, and Guo et al reviewed the advancement of the three main aspects of biomass-based, graphene-based, and hydrogel-based, respectively, photothermal materials for an SSG system. This review aims to provide a comprehensive and critical overview of an SSG system with a focus on designs and engineering of materials for enhanced light-to-heat conversion in the application of solar water purification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional solar distillation, ISSG cuts down the heat loss via localizing the solar heat near the surface of the evaporator. Up to now, numerous materials including metal nanoparticles 3 5 , carbonaceous materials 6 8 , two-dimensional (2D) materials 7 , 9 11 , hydrogels 12 14 were explored as evaporators. Meanwhile, many effective methods have also been proposed to enhance the evaporation rate, concerning three-dimensional (3D) ISSG 15 20 , multistage evaporation 21 24 , water supply control 25 , 26 , synergy with chemical phase change 27 29 and electrothermal effect 30 , 31 , reduction of evaporation enthalpy 12 , 13 , 32 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of oily wastewater discharged from our daily life, industries, or spill accidents has caused great harm to the environment, ecology, and even human health. [1][2][3][4][5] Such pollution has come up an urgent need to treat oily wastewater properly. In general, oily wastewater can be divided into immiscible oil/water mixtures and emulsions.…”
mentioning
confidence: 99%